Peer mentoring in an extracurricular music class. (November 2021) - Goodrich, Andrew
The purpose of this study was to explore how high school students mentored beginning fifth-grade students in an extracurricular music class for double-reed instruments. In this study, I investigated the role of peer mentoring with how high school mentors shared their knowledge and experiences, and the role of the teacher in this process. The following questions guided this study: How did the participants share their knowledge and experiences during peer mentoring? How did the teacher serve as a guide for the student participants during peer mentoring? Data collection included observations and interviews during one semester of instruction, and analysis of the data collected involved a system of coding from which two themes developed: mentoring concurrent with director teaching and learning while mentoring. In addition, findings indicated that the participants used knowledge learned from outside sources, they reinforced content presented by the teacher, and they drew on their own musical knowledge during the process. Under the guidance of the teacher, the participants also learned how to share their knowledge that in turn helped elevate their individual levels of musicianship. Implications for music teachers suggest the use of peer mentoring to help create meaningful learning experiences in their classrooms and increase interaction among students.